Methodology and Factors Consideration for Effective Building Web-based Business Applications - Abdul-Aziz, Azlianor; Koronios, Andy; Gao, Jing; Sulong, Muhammad Suhaizan (2011)
Internet has become a place for information publishing and sharing. Nowadays, web-based business applications serve as a gateway to access information and to communicate globally compared with conventional system that limits access. The nature of web environment gives the web-based business applications unique to its own kind. This paper discusses the unique characteristics of these applications that determine types of web-based business applications with the need of special requirements when building such applications. Next, the development methodology on how the web-based business applications are built is described and some success factors of building such applications are discovered. The paper provides a comprehensive methodology and factors for developers to consider effectively building web-based business applications. Further work will be carried out to investigate insightful understanding of issues and challenges that encountered by developers in particular and by web development team in general through conducting case studies.